2023
DOI: 10.3389/fgene.2022.1076035
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rare thalassemia variants using third-generation sequencing

Abstract: Routine PCR, Sanger sequencing, and specially designed GAP-PCR are often used in the genetic analysis of thalassemia, but all these methods have limitations. In this study, we evaluated a new third-generation sequencing-based approach termed comprehensive analysis of thalassemia alleles (CATSA) in subjects with no variants identified by routine PCR, Sanger sequencing, and specially designed GAP-PCR. Hemoglobin testing and routine PCR tests for 23 common variants were performed for 3,033 subjects. Then, Sanger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This is promising for NIPT. It has been reported that deletion and point mutation of HBA1, HBA2, and HBB can be directly obtained by TGS (Liu et al 2022;Liang et al 2021). Application of TGS for HBB in NIPT had been reported (Jiang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is promising for NIPT. It has been reported that deletion and point mutation of HBA1, HBA2, and HBB can be directly obtained by TGS (Liu et al 2022;Liang et al 2021). Application of TGS for HBB in NIPT had been reported (Jiang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, long-read thirdgeneration sequencing (TGS) has emerged as a powerful tool to detect the genetic basis of α-and β-thalassemia, especially for detecting complex structural variants and CNVs. TGS offers a convenient way to directly analyze parental haplotypes by utilizing ultra-long read lengths of up to 30 kb-100 kb, providing high accuracy (QV30 > 99.9%), single-molecule resolution, and no GC preference (Liang et al 2023;Liu 2022). This technology may improve the detection rate of NIPT in thalassemia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their potential, these techniques have not been integrated into clinical practice, and their utilization in research studies remains limited. Advantages over second-generation sequencing methods include the fact that they do not require sample pre-amplification and can read longer fragments of DNA, but the error rate is generally higher (10–15%) [ 58 , 59 , 60 , 61 ].…”
Section: Gastric Cancer Characterization Prognosis and Management In ...mentioning
confidence: 99%
“…The findings suggest that rare thalassemia variants are more prevalent than previously thought and are often misdiagnosed by conventional diagnostic methods. Liu et al (29) conducted CATSA tests on 49 subjects who were negative for specially designed GAP-PCR and Sanger sequencing tests and identified mutations in the thalassemia gene in 8 subjects, indicating a higher positive detection rate of CATSA. The general process flow, advantages and disadvantages for screening and diagnosing thalassemia using conventional, NGS and TGS approaches.…”
Section: Tgs In the Molecular Screening Of Thalassemia Carriersmentioning
confidence: 99%